Progressive scale implementation for personal income tax as a necessary condition for ensuring social justice - N. Z. Zotikov (Вестник университета, 2024)
The purpose of the study is to examine the role and importance of this tax when forming revenues of consolidated budgets of the constituent entities of the Russian Federation in the context of federal districts, and its impact on the formation of indicators characterizing the social sphere, as well as to analyze the positive foreign experience of personal income taxation. The general scientiﬁc methods of cognition (analysis, synthesis, generalization, grouping, comparison, tabular, etc.) were used. The study is based on ofﬁcial data of the Federal State Statistics Service and the Federal Tax Service of the Russian Federation. It has been established that personal income tax fulﬁlls its ﬁscal function, and it is the main source of income of local budgets and regions. As for the social function, it is currently lost. It is reﬂected in the following: in four federal districts, where about half of the country’s population lives, wages are below the average Russian level; the coefﬁcients of funds and Gini coefﬁcient are not improving; deductions and beneﬁts on personal income tax do not fulﬁll the social function, social justice is not ensured, and social stratiﬁcation of society is increasing. In the context of the current unfavorable demographic situation and external challenges due to Western sanctions, it is necessary to strengthen motivation to work, considering foreign positive experience to introduce a real and workable progressive scale of personal income taxation.